Life Finds a Way: Young Adults With Lesbian Mothers Reflect on Their Childhood Prior to Legal Recognition of Same-Sex Parents in Sweden - Malmquist, Anna; Andersson, Sandra; Salomonsson, Julia (Frontiers in Psychology, 2020)
The strapline “life finds a way”, from the classic movie Jurassic Park, referred to how the all-female dinosaurs in a theme park had been able to reproduce, despite the laws of nature. Similarly, the participants in the present study described how their lesbian mothers had shown that “life finds a way”, when having children and forming a family life, prior to the legal recognition of same-sex parents in Sweden. The study draws on interviews with eight young Swedish adults, aged 17 to 30 (average age 25). They had been raised by lesbian couples but were born prior to the legal recognition of same-sex parenthood. Prior to a legal change in 2003, a same-sex couple could not share legal parenthood. Further, female couples were excluded from Swedish assisted reproduction programs until 2005. The interviews have been analyzed thematically, and the article presents the results in four themes. The first theme, circumvent, oppose, or adapt to legal obstacles, shows the participants’ reflections on how their parents navigated legal obstacles in order to have children and to live together as a family. The second theme, legal obstacles do not affect everyday life, depicts a common experience of how a lack of legal recognition seldom mattered to the participants during their childhood. Rather, they explained how their parents had been able to form parenthood and close relations without legal recognition. In contrast, the third theme describes occasions when legal parenthood matters. This theme highlights occasions when the lack of legal parenthood was problematic or devastating for the participants, such as when parents divorced, or one parent died. The final theme, the meaning of legal parents in adulthood, explores the participants’ reflections on the meaning and impact of legal ties (or lack of legal ties) between themselves as young adults and their parents. The findings are discussed in relation to previous research on children and young adults with same-sex parents.